Natural Disasters in Nigeria: An Econometric Model - Okon, Emmanuel Okokondem (American International Journal of Social Science Research, 2018)
This paper models and estimates the occurrence of natural disaster in Nigeria using the residual-based test for cointegration within an autoregressive distributed lag (ARDL) framework and error correction specification between the period 1970 and 2016, the results from the estimated static model shows that DLOG(TEM), LOG(GDPC) and LOG(URB) are long-run determinants of natural disasters in Nigeria. The short run error correction model results revealed that the coefficients of DLOG(CO2), DLOG(WIS), LOG(GDPC), LOG(URB), DLOG(GDPC(-2)) and LOG(URB(-1))seem to be significant and helpful in explaining the occurrence of natural disaster (NAD)in Nigeria. The error correction term shows that speed of adjustment of disequilibrium in natural disaster (NAD) in the previous year which is corrected in the current year is about 44.3 percent. Therefore, Nigerian government should among other recommendations embark on reducing urbanization growth by making sure that industries which forge linkages with rural occupations should be promoted to mitigate a high rural-urban migration. Establishing of very effective early warning systems for meteorological, geophysical, biological, social and industrial hazards should be ensured.